2017
DOI: 10.1007/s10120-017-0724-7
|View full text |Cite
|
Sign up to set email alerts
|

The value of diagnostic endoscopic submucosal dissection for patients with clinical submucosal invasive early gastric cancer

Abstract: The stomach was preserved in 28.8% of patients, and preceding ESD did not show obvious disadvantages. Therefore, diagnostic ESD should be considered as an initial treatment for limited cT1b gastric cancer cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 22 publications
1
12
0
1
Order By: Relevance
“…However, studies analyzing pathologic results of patients who underwent gastrectomy due to preoperatively suspected submucosal invasion reported that 28.8%-43.0% of these lesions could have been treated with endoscopic resection. 110,111 Therefore, further research is needed regarding treatment methods for preoperatively suspected submucosal invasive early gastric cancer.…”
Section: Statement G3: We Recommend Endoscopic Resection For Early Gamentioning
confidence: 99%
“…However, studies analyzing pathologic results of patients who underwent gastrectomy due to preoperatively suspected submucosal invasion reported that 28.8%-43.0% of these lesions could have been treated with endoscopic resection. 110,111 Therefore, further research is needed regarding treatment methods for preoperatively suspected submucosal invasive early gastric cancer.…”
Section: Statement G3: We Recommend Endoscopic Resection For Early Gamentioning
confidence: 99%
“…Some literature referred to the relationship between a waiting duration and the hardness of adhesion in repeat surgeries, while others suggested that this made the repeated surgery easier due to its loosening [6,7]. Furthermore, we have previously published that a wait time of fewer than 6 months may be acceptable in cStage I gastric cancer [8]. Performing surgery within this time may minimize associated surgical risks that arise from an adhesion.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that the incidence of LNM in differentiated lesions <3 cm with SM1 invasion was significantly higher than that of the absolute standard ( P = 0.004), indicating that SM1‐invasive differentiated EGC should be balanced against the risks related to surgery due to their increased risk of LNM. In 2017, the concept of diagnostic ESD was proposed for clinically submucosal invasive EGC . In that study, Fujiya et al compared the overall survival (OS) and cause‐specific survival (CSS) between patients undergoing ESD and a radical gastrectomy for clinically diagnosed differentiated EGC with SM1 invasion and of 3 cm in diameter or smaller.…”
Section: Endoscopic Resection Indications For Egcmentioning
confidence: 99%